The Role of β-1.3/1.6-D-Glucan From Ganoderma lucidum Mycelium Extract in Ulcerative Colitis - Marcellus Simadibrata; Aditya Rachman; Saskia Aziza Nursyirwan; Murdani Abdullah; Rabbinu Rangga Pribadi; Raja Mangatur Haloho; Anthony Eka Wijaya; Daniel Martin Simadibrata; Kaka Renaldi (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2021)
Ulcerative colitis (UC) is an idiopathic inflammatory disease that affects the colon. Current pharmacological modalities to treat UC have various side effects; therefore, there is a demand to develop a new alternative medicine that can reduce side effects and increase drug efficacy. One candidate for alternative therapy is Polysaccharide Peptide which is extracted from Ganoderma lucidum mycelium. This Polysaccaharide has an active compound of Β-1,3/1,6-D-Glucan which has strong immunomodulatory and anti-inflammatory properties. Various studies have reported that Ganoderma lucidum polysaccharides can reduce inflammatory markers such as TNF-α, IFN-γ, and IL-17A, which is produced by colonic mucosal inflammation. In addition, β-1,3/1,6-D-Glucan has shown improvements in inflammatory parameters and intestinal immunological barrier function animal studies with artificial colitis and requires further research in humans before clinical applications.